ERRORS ANAYSIS OF PLANAR INTERNAL GEAR SINGLE-ENVELOPING CROWN WORM DRIVE - SUN ShuMin; WANG JinGe; CHEN YongHong; WANG Shuang (Jixie qiangdu)
In order to grasp the actually meshing of planar internal gear single-enveloping crown worm drive,the errors analysis is developed. Base on the gear meshing theory,the meshing geometry with errors of this worm drive is established,and the accurate 3D model is constructed. The tooth surface meshing status of this worm drive under the ideal conditions are studied,and the actually meshing status of this worm drive with the centre distance error and inclination angle error are studied. The results show that: there are five pairs tooth surface are contemporary meshing,and the contact lines are straight line,as well as the contact lines are average distributed and along the tooth height; the negative values of centre distance error and worm axial displacement error are better than the true values of those; the shaft angle error,the inclination angle error and the base circle radius error are seriously affect the actual meshing status of the planar internal gear single-enveloping crown worm drive.